Prostate-specific antigen (PSA) screening rates and factors associated with screening in Eastern Canadian men: Findings from cross-sectional survey data - Tchir, Devan; Farag, Marwa; Szafron, Michael (Canadian Urological Association Journal, 2020)
Introduction: The prostate-specific antigen (PSA) test is used in Canada to detect prostate cancer (PCa) despite mixed recommendations. Complications arising from false-positives are common, posing as a cancer-screening concern. This work estimates some Canadian rates of PSA screening and identifies men at increased odds for PSA screening. Methods: The Canadian Community Health Survey (CCHS) from 2009/10 (Atlantic Canada; ATL), 2011/2012 (Ontario; ON), and 2013/2014 (Quebec; QC) were used. Lifetime and recent PSA screening with confidence intervals were constructed to estimate PSA screening in ATL, ON, and QC. Two logistic regression models (for men <50 and ≥50 years of age) were used to determine associations between factors and lifetime PSA screening. Results: PSA screening rates have increased in most age groups for ATL, ON, and QC since 2000/2001. Factors positively associated with lifetime PSA screening in men of all ages were: having a digital rectal exam, having a regular doctor, and having a colorectal exam. Fruit and vegetables consumption and non-smoking status were positively associated with lifetime PSA screening in men <50 years of age. High income and the presence of chronic health conditions were positively associated with lifetime PSA screening in men ≥50 years of age. Conclusions: PSA screening rates have generally increased since 2000/2001 in Canada. Physician-related factors play a role in men at all ages, while different factors are associated in men <50 years of age and men ≥50 years of age. Limitations include the generalizability to all of Canada and the potential for recall bias.